Desenvolvimento de um biossensor bienzimático amperométrico para detecção de β-lactose através de filmes nanoestruturados layer-by-layer (LbL) - Campos, Paula Pereira (2014)
In this work the immobilization of enzyme β-Galactosidase has been investigated with use of assembly technique of nanostructured films denominated LbL (Layer-by-Layer) for employment in an amperometric biosensor of lactose. Therefore, spectroscopy measured has made for UV-vis (Ultraviolet-visible) and fluorescence, in order to monitor the bands of absorption and emission of each bilayer deposited and to confirm the presence of enzyme in the films. It has made too FTIR (Fourier Transform Infrared Spectroscopy) and SFG (Sum Frequency Generation) for the purpose to understand the films structure, the interactions present and the efficiency of technique in the immobilization process. For the lactose detection amperometric measured have carried and that way the performance of modified electrode have evaluated in relation to enzyme immobilization, the polyelectrolytes performance Poly (allylamine hydrochloride) (PAH) and Poli (etileno imina) (PEI) and poly(ethyleneimine) and the operations conditions of biosensor which sensibility, limit of detection, interferences and stability. The evaluation of enzyme deposition by UV-vis and fluorescence showed that the films growth has been satisfactory presenting the characteristics bands of da β-Gal regarding to amino acid residues tryptophan, tyrosine and phenylalanine, among others, in λ = 280 nm for absorption and λ = 344 nm for emission and the deposition of material has been growing. The spectrum of FTIR and SFG indicated bands of chemical groups characteristics of polymers and enzyme and proved that the bonds, probably secondary of the elements are sufficiently strong for to keep the films in substrate during the sensory evaluation. In lactose detection it has made electrode of (PEI/β-Gal)n e (PAH/β-Gal)n both of ten and third bilayers. The sensibility of film (PEI/β-Gal)10 was 0.061 μA mmol-1 cm-2, while the (PAH/β-Gal)10 was 0.079 μA mmol-1 cm-2. In order to increase the efficiency of the biosensors, electrodes compounds for third bilayers were tested, this way the film (PEI/β-Gal)30 has achieved a sensibility higher than the previous electrodes of 0.31 μA mmol-1 cm-2, is likely that a great amount of enzyme has been immobilized. However, the film ITO/PB/(PAH/β-Gal)30 has not get the same efficiency despite de number of bilayer have been increase. Have been identified two interferences, the glucose and the ascorbic acid, but both can be avoided, the first with use of a biosensor for glucose coupled with lactose biosensor and the second causes an elevation on current, being naturally differentiated. The stability of the biosensor was twelve days, being measured in days alternate. All experiments performed to converge to prove that the LbL technique were adequate to assembly the biosensor and that lactose detection can be done and in levels nearby to real samples, but is possible to improve the system still with studies more expanders about the films structure and to test news biosensors configurations.